x+(y+3)=13

Simple and best practice solution for x+(y+3)=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+(y+3)=13 equation:


Simplifying
x + (y + 3) = 13

Reorder the terms:
x + (3 + y) = 13

Remove parenthesis around (3 + y)
x + 3 + y = 13

Reorder the terms:
3 + x + y = 13

Solving
3 + x + y = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + x + -3 + y = 13 + -3

Reorder the terms:
3 + -3 + x + y = 13 + -3

Combine like terms: 3 + -3 = 0
0 + x + y = 13 + -3
x + y = 13 + -3

Combine like terms: 13 + -3 = 10
x + y = 10

Add '-1y' to each side of the equation.
x + y + -1y = 10 + -1y

Combine like terms: y + -1y = 0
x + 0 = 10 + -1y
x = 10 + -1y

Simplifying
x = 10 + -1y

See similar equations:

| 5x-14=19-6x | | v=17*2*1 | | (3x)w=30 | | 2+6x+x=30 | | 2.1x-1=x+11.1 | | X^2-4x-500=0 | | 21=-x | | x+(2x+15)+(x+15)=180 | | -4+4x-5x=1 | | 6X-11=8X+10 | | .2x+9+.8x=-11 | | 12m+6n-5m+8n= | | k=v+29 | | 4(x+9)+3=9x-5(x-3) | | -5(x+4)+98=28+10 | | 10a=7 | | 2y+12=-2 | | -5x+10+4x=0 | | 2a+3b-c=18 | | 3x=-2x^2 | | 2X+94=10X-10 | | -3x-(-4)=3x+10 | | 123456789012345678901234567890+98765432109876543210987654321= 222222221122222222112222222211 | | 15+15x=180 | | (3x-5)(3x-5)=26 | | 0=x^2+0.0129x-0.00404 | | 8x-2=-9+yx | | 5x^4*8x^6= | | 4x-5+x=15 | | -3y+38.9=1.4 | | 0=x^2-0.768x+0.1475 | | 3+5x=6x+1 |

Equations solver categories